2021
DOI: 10.1177/2192568220986144
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Facet Tropism on Postoperative Cervical Range of Motion After Single-Level Cervical Disc Arthroplasty

Abstract: Study Design: Retrospective analysis. Objectives: Cervical disc arthroplasty (CDA) was designed to replace the degenerated disc with the prosthesis to preserve cervical motion. The commonly used artificial discs are designed symmetric, whereas the facet joints were reported to be asymmetric in many people. This study aimed to evaluate the effect of facet tropism on the cervical range of motion (ROM) after single-level CDA using Prestige LP. Methods: A total of 90 patients who underwent single-level CDA using P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 60 publications
0
11
1
Order By: Relevance
“…In relation to angular movement, these findings differ from some previous studies where tropism was found to be related to mobility, at least in flexion/extension in the lumbar [14] and cervical spines [5]. Methodological differences could account for the findings being different from other studies.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In relation to angular movement, these findings differ from some previous studies where tropism was found to be related to mobility, at least in flexion/extension in the lumbar [14] and cervical spines [5]. Methodological differences could account for the findings being different from other studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Even in those studies that measured the asymmetry from 3D images, most measured tropism from single two-dimensional slices [8,13]. A difficulty with this method is that the angles of the facets can be different depending on which slice is measured [5,8]. To overcome this difficulty, Liu et al [5] fit a single plane to each facet but still calculated asymmetry in each cardinal axis separately.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations